UPAYA PENINGKATAN SELF-ESTEEM PADA DEWASA MUDA PENYITAS KEKERASAN DALAM PACARAN DENGAN COGNITIVE BEHAVIOR THERAPY - Pratiwi, Pradipta Christy (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2017)
Abstract — Dating violence, which frequently occurs among early adults, can manifest itself in many forms, including physical, psychological, and sexual abuse. A significant impact of dating violence is the decrease of self-esteem of the victims. It is also the cause of difficulties for the victims to break out of the cycle of violence. The present study intends to employ cognitive behaviour therapy (CBT) to enhance the self-esteem of early adults who suffers from dating violence. The research design used in the present study was quasi-experimental one-group pre-test post-test design. Three subjects were acquired through purposive sampling for the present study. The effectivity of the therapy was inferred from qualitative evaluation (improvement of self-esteem score, observation, and interview). Instruments used in the present study were Rosenberg Self-Esteem Scale (RSES) to assess self-esteem and Revised Conflict Tactics Scale (CTS-2) to assess the characteristics of violence. The results indicated a higher score in RSES. Further evaluation also demonstrated considerable changes of subjects’ cognitive, affective, and behavioural aspects. Given all the results, CBT is considered to be an effective intervention to enhance the self-esteem among victims of dating violence.  Abstrak — Kekerasan dalam pacaran, sering dijumpai pada dewasa muda, dapat terjadi dalam bentuk kekerasan fisik, kekerasan psikologis, dan kekerasan seksual. Dampak signifikan dari kekerasan dalam pacaran adalah rendahnya self-esteem penyitas. Hal ini juga yang menyebabkan penyitas sulit keluar dari siklus kekerasan. Penelitian ini bertujuan untuk melakukan intervensi Cognitive Behavior Therapy (CBT) pada dewasa muda penyitas kekerasan dalam pacaran untuk meningkatkan self-esteem mereka. Desain penelitian ini adalah one-group pre-test-post-test design (kuasi eksperimen). Jumlah sampel ialah tiga orang, diperoleh dengan teknik purposive sampling. Efektivitas terapi dilihat dari evaluasi kualitatif (penambahan skor RSES, observasi, dan wawancara). Alat ukur yang digunakan adalah Rosenberg Self-esteem Scale (RSES) untuk mengukur self-esteem dan Revised Conflict Tactics Scale (CTS2) untuk mengetahui karakteristik kekerasan yang dialami penyitas. Hasil penelitian menunjukkan peningkatan skor pada RSES. Selain itu, evaluasi kualitatif juga menunjukkan peningkatan positif aspek kognitif, afektif, dan perilaku subjek penelitian. Oleh karena itu, CBT dapat dikatakan efektif meningkatkan self-esteem pada penyitas kekerasan dalam pacaran.